Higher Education governance and policy in Spain - Francisco Rubio; Carlos Llopis-Albert; Shouzhen Zeng; Dayanis García-Hurtado (Multidisciplinary Journal for Education, Social and Technological Sciences)
The knowledge society of the 21st century is undergoing important changes in the field of information, communication, and globalization, which has led Higher Education Institutions (HEIs) to play a leading role in its sustainable development, based on three fundamental pillars: social, economic, and environmental, which go beyond its traditional role based on training students to obtain a professional degree.